Evaluation of Risk Culture Implementation in the Digital Investment Company PT XYZ - Fanny Wiryana; Tubagus Muhammad Yusuf Khudri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to evaluate the risk culture at digital investment company PT XYZ using the The Institute of Risk Management (IRM) 2012 framework. The research employs a case study design with a qualitative approach. Data were collected through semi-structured interviews and surveys. At the individual level, analysis was conducted using the Risk Type Compass and Moral DNA instruments. The Risk Type Compass results indicate that employees at PT XYZ tend to exhibit a relatively balanced tolerance across most risk types. PT XYZ shows a combination of adventurous–deliberate traits (bold yet calm and stable) as well as prudent–intense tendencies (careful and conscientious). Based on the Moral DNA analysis, employees at PT XYZ demonstrate a predominant inclination toward reason ethics in their decision-making processes. At the organizational level, analysis through interviews and the Double S Model shows that PT XYZ’s culture falls into the communal category, indicating high levels of social cohesion and solidarity within the organization. Furthermore, evaluation using the eight aspects of the IRM Risk Culture Aspects Model reveals several areas that require improvement, specifically in the following aspects Risk Leadership, Responding to Bad News, Risk Governance, and Risk Resources. Meanwhile, the aspects that are already considered to be relatively strong include Risk Transparency, Risk Competence, Risk Decisions, and Rewarding Appropriate Risk Taking.